2000
DOI: 10.1007/s002800000115
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation and pharmacokinetic study of irinotecan in combination with paclitaxel in patients with advanced cancer

Abstract: The recommended dose of irinotecan on this schedule is 50 mg/m2. The sequence of drug administration affects neither the elimination of irinotecan nor the chemotherapy-related toxicity. This combination is well tolerated and causes minimal clinical side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This less thrombocytopenic regimen may also be helpful in the treatment of elderly patients. A phase I study of Pac and CPT combination chemotherapy showed that neutropenia was dose-limiting, and Pac 75 mg/m 2 and CPT 50 mg/m 2 were recommended [27]. The difference in the recommended dose between that study and ours can be attributed to the fact that we used prophylactic G-CSF when monocytopenia developed after the start of chemotherapy.…”
Section: Discussionmentioning
confidence: 81%
“…This less thrombocytopenic regimen may also be helpful in the treatment of elderly patients. A phase I study of Pac and CPT combination chemotherapy showed that neutropenia was dose-limiting, and Pac 75 mg/m 2 and CPT 50 mg/m 2 were recommended [27]. The difference in the recommended dose between that study and ours can be attributed to the fact that we used prophylactic G-CSF when monocytopenia developed after the start of chemotherapy.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, Murren et al . conducted a dose escalation study for advanced cancers and RDs of weekly paclitaxel at 75 mg/m 2 and weekly irinotecan at 50 mg/m 2 18 . Rushing et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Murren et al conducted a dose escalation study for advanced cancers and RDs of weekly paclitaxel at 75 mg/m 2 and weekly irinotecan at 50 mg/m 2 . 18 Rushing et al also conducted Phase I/ II studies for advanced small cell lung cancer and RDs of weekly paclitaxel at 50 mg/m 2 and weekly irinotecan at 60 mg/m 2 , at which the efficacy rate was 75%. 19 Based on the above findings, we investigated the dose level and safety of combined therapy with irinotecan and paclitaxel by weekly administration in a Phase I study, followed by clinical effects in a Phase II study.…”
Section: Discussionmentioning
confidence: 99%
“…Rosen et al also reported that dose escalation of the two drugs above the starting dose (irinotecan 225 mg/m 2 and paxlitaxel 100 mg/m 2 , once every 3 weeks) was impossible because of neutropenic fever or severe diarrhea [14]. On the other hand, Murren et al investigated the combination of the two drugs in a weekly schedule for patients with advanced various cancers, and concluded that this combination was well tolerated, although they experienced several adverse events in the patients treated with the recommended dose [15]. These results suggest that the combination of irinotecan and paclitaxel produces relatively severe toxicities, compared with other regimens containing irinotecan or paclitaxel such as cisplatin plus irinotecan or carboplatin plus paclitaxel [5,16].…”
Section: Discussionmentioning
confidence: 99%